Nitrous oxide emission factors for cattle dung and urine deposited onto tropical pastures: A review of field-based studies - Zhu, Yuhao; Butterbach-Bahl, Klaus; Merbold, Lutz; Leitner, Sonja; Pelster, David E. (Elsevier, 2021)
Livestock excreta on pastures is an important source of nitrous oxide (N 2 O) emissions, however studies measuring these emissions in tropical regions, particularly Africa, remain limited. Therefore we measured N 2 O emissions from different quantities of dung patches during three observation periods (dry, wet and transition from dry to wet season) and different volumes of urine patches during wet and dry seasons. Dung patches did not stimulate soil N 2 O emissions in any of the three observation periods, while urine application stimulated soil N 2 O emissions during both seasons, with higher emissions observed during the wet season. The dung EFs (0.00–0.03%) and the urine EFs (0.04–0.40%) showed no detectable effects of dung quantity or urine volume. We further synthesized observations from other studies in wet and dry tropical regions, which indicated that the excreta N 2 O EFs were similar to the default values provided in the IPCC 2019 refinement (0.11% vs 0.07% for dung and 0.41% vs 0.32% for urine in dry climates, and 0.13% vs 0.13% for dung and 0.65% vs 0.77% for urine in wet climates). However, sub-Saharan African (SSA) studies had consistently lower EFs, possibly due to the lower urine-N: dung-N ratio in SSA compared with the other tropical regions, suggesting that the refinement may still overestimate excreta emissions in SSA. Moreover, considering the large variations in the summarized tropical excreta N 2 O EFs, from -0.01 to 1.77% for dung and 0.00 to 4.90% for urine, more studies under diverse conditions across tropical regions are recommended. • Excreta N 2 O emission factors not influenced by mass or volume. • Soil type and N partitioning are overlooked factors in national N 2 O inventories. • IPCC 2019 refinement may still overestimate excreta N 2 O emissions in SSA.